The Notion of Stability of a Differential Equation and Delay Differential Equation Model of HIV Infection of CD4+ T-Cells - Normah Maan; Izaz Ullah Khan; Nor Atirah Izzah Zulkefli (North Atlantic University Union, 2024)
INTERNATIONAL JOURNAL OF MATHEMATICS AND COMPUTERS IN SIMULATION DOI: 10.46300/9102.2021.15.4